Models are likely to underestimate increase in heavy rainfall in the extratropical regions with high rainfall intensity. Issue 14 (18th July 2017) - Borodina, Aleksandra; Fischer, Erich M.; Knutti, Reto
Abstract: Model projections of regional changes in heavy rainfall are uncertain. On timescales of few decades, internal variability plays an important role and therefore poses a challenge to detect robust model response in heavy rainfall to rising temperatures. We use spatial aggregation to reduce the major role of internal variability and evaluate the heavy rainfall response to warming temperatures with observations. We show that in the regions with high rainfall intensity and for which gridded observations exist, most of the models underestimate the historical scaling of heavy rainfall and the land fraction with significant positive heavy rainfall scalings during the historical period. The historical behavior is correlated with the projected heavy rainfall intensification across models allowing to apply an observational constraint, i.e., to calibrate multimodel ensembles with observations in order to narrow the range of projections. The constraint suggests a substantially stronger intensification of future heavy rainfall than the multimodel mean. Key Points: In the regions with high heavy rainfall intensity, many models underestimate the response of heavy rainfall to warming temperatures In the regions with high heavy rainfall intensity, many models underestimate the land fraction with significantly positive scalings of heavy rainfall Applying an observational constraint yields higher future heavy rainfall intensification than projected by the CMIP5 mean